Lectotype and neotype designations in Dodecastichus Stierlin, 1861 and Otiorhynchus Germar, 1824 (Coleoptera: Curculionidae). - Magnano, Luigi (Contributions to Entomology = Beiträge zur Entomologie, 1998)
Lectotypes of the following species are designated: Dodecastichus heydeni Stierlin, 1861; Otiorhynchus (Acunotus) lutosus Stierlin, 1858; O. (Amosilnus) oberti Faust, (1886); O. (Arammichnus) dobrutschae Stierlin, 1882; O. (Aranihus) misellus Stierlin, 1861; O. (Aranihus) riguus Stierlin, 1883; O. (Choilisanus) affinis Hochhuth, 1847; O. (Choilisanus) caroli Stierlin, 1893; O. (Choilisanus) caucasicus Stierlin, 1872; O. (Choilisanus) schoenherri Stierlin, 1877; O. (Choilisanus) viridisetosus Stierlin, 1905; O. (Egydelenus) jaltensis Formanek, 1926; O. (Elechranus) banaticus Stierlin, 1861; O. (Elechranus) chalceus Stierlin, 1861; O. (Elechranus) roubali Penecke, 1931; O. (Ergiferanus) mus Stierlin, 1862; O. (Lolatismus) chaudoiri Hochhuth, 1851; O. (Lolatismus) depressus Stierlin, 1875; O. (Melasemnus) brevipennis Stierlin, 1892; O. (Melasemnus) crucirostris Hochhuth, 1851; O. (Meriplodus) laconicus Kirsch, 1880; O. (Mitomiris) astutus (Faust, 1886); O. (Mitomiris) laniger Faust, 1887; O. (Namertanus) pseudomias Hochhuth, 1847; O. (Nihus) proximus Stierlin, 1861; O. (Nubidanus) punctirostris Stierlin, 1883; O. (Nubidanus) ruminalis Faust, 1894; O. (Osmobodes) rutilipes Hochhuth, 1851; O. (Osmobodes) tenuimanus Faust, 1890; O. (Osmobodes) venalis Faust, 1888; O. (Otiomimus) desbrochersi Stierlin, 1883; O. (Otiorhynchus) amabilis Stierlin, 1861; O. (Otiorhynchus) auropupillatus Stierlin, 1861; O. (Otiorhynchus) delatus Faust, 1899; O. (Otiorhynchus) latissimus Stierlin, 1861; O. (Otiorhynchus) scaberrimus Stierlin, 1861; O. (Otiorhynchus) steppensis Faust, 1888; O. (Otismotilus) auroguttatus Stierlin, 1879; O. (Paracryphiphorus) nuncius Faust, 1890; O. (Petalorrhynchus) crinitarsis Stierlin, 1861; O. (Phalantorrhynchus) patruelis Stierlin, 1861; O. (Phalantorrhynchus) planidorsis Stierlin, 1886; O. (Pliadonus) schneideri Stierlin, 1876; O. (Tournieria) siewersi Faust, 1888; O. (Podonebistus) alaianus Stierlin, 1886; O. (Podonebistus) bleusei Faust, 1899; O. (Podonebistus) cylindricus Stierlin, 1877; O. (Podonebistus) nefandus Faust, 1888; O. (Podonebistus) prostratus Heyden, 1886; O. (Podonebistus) subparallelus Stierlin, 1893; O. (Prototis) popovi Faust, 1888; O. (Provadilus) carbonarius Hochhuth, 1847; O. (Pseudocryphiphorus) argillosus Hochhuth, 1851; O. (Pseudocryphiphorus) irritabilis (Faust, 1886); O. (Pseudocryphiphorus) zebei Stierlin, 1861; O. (Rimenostolus) auripes Stierlin, 1875; O. (Rusnepranus) arenosus Stierlin, 1861; O. (Rusnepranus) heerii Stierlin, 1858; O. (Stupamacus) erroneus (Faust, 1886); O. (Stupamacus) infensus Faust, 1888; O. (Stupamacus) pilosulus Penecke, 1928; O. (Tournieria) cornicinus Stierlin, 1861; O. (Tournieria) emgei Stierlin, 1887; O. (Tournieria) lubriculus Faust, 1890; O. (Udonedus) koenigi Faust, 1888; O. (Urorrhynchus) truncatus Stierlin, 1861; O. (Zariedus) hystericus Faust, 1892; O. (Zariedus) sedulus Faust, 1894. Neotypes are designated for O. (Amosilnus) pityophilus Gistel, 1857 and of O. (Postaremus) gelidus Gistel, 1857. The following new synonymies (synonyms in square brackets) are established: O. velutinus Germar, 1824 [= O. desbrochersi Stierlin, 1896 (not O. desbrochersi Stierlin, 1883)]; O. laconicus Kirsch, 1880 [= O. oertzeni Stierlin, 1883]; O. nodosus (O. F. Müller, 1754) [= O. gelidus Gistel, 1857]; O. lavandus Germar, 1824 [= O. pityophilus Gistel, 1857]; O. proximus Stierlin, 1861 [= O. depilis Smreczynski, 1959]; O. parvicollis Gyllenhal, 1834 [= O. riguus Stierlin, 1883]; O. caucasicus Stierlin, 1872 [= O. viridisetosus Stierlin, 1905]. Otiorhynchus erroneus (Faust, 1886) is attributed species rank. Otiorhynchus affinis Hochhuth is removed from the synonymy with O. incivilis Faldermann, 1838; O. auroguttatus Stierlin is removed from the synonymy of O. heerii Stierlin, 1858 and transferred from O. (Rusnepranus) Reitter, 1912 to O. (Otismotilus) Reitter, 1912. New combinations are: Otiorhynchus (Rimenostolus) auripes Stierlin from O. (Panorosemus) Reitter, 1913; O. (Rusnepranus) heerii Stierlin from O. (Otismotilus) Reitter, 1912; O. (Stupamacus) infensus Faust from O. (Microphalantus) Reitter, 1912; O. (Elechranus) roubali Penecke from O. (Cryphiphorus) Stierlin, 1883; O. (Pliadonus) siewersi Faust, 1888 from O. (Melasemnus) Reitter, 1912; O. (Podonebistus) alaianus Stierlin, O. (Cryphiphorus) argillosus Hochhuth, O. (Lolatismus) depressus Stierlin, O. (Ergiferanus) mus Stierlin, O. (Podonebistus) prostratus Heyden, O. (Pliadonus) schneideri Stierlin, and O. (Osmobodes) venalis Faust, all thus far listed as species incertae sedis. Nomenclatural Actsheydeni (Stierlin, 1861) (Dodecastichus), Lectotype described as Otiorhynchus heydenidebilis Smreczynski, 1959 (Otiorhynchus), syn. n. of Otiorhynchus (Nihus) proximus Stierlin, 1861oertzeni Stierlin, 1883 (Otiorhynchus), syn. n. of Otiorhynchus (Meriplodus) laconicus Kirsch, 1880lutosus Siterlin, 1858 (Otiorhynchus (Acunotus)), Lectotypeoberti (Faust, 1886) (Otiorhynchus (Amosilnus)), Lectotype described as Brachyrrhinus obertipityophilus Gistel, 1857 (Otiorhynchus (Amosilnus)), Neotype; syn. n. of Otiorhynchus lavander Germar, 1824dobrutschae Stierlin, 1882 (Otiorhynchus (Arammichnus)), Lectotypemisellus Stierlin, 1861 (Otiorhynchus (Aranihus)), Lectotyperiguus Stierlin, 1883 (Otiorhynchus (Aranihus)), Lectotype; syn. n. of Otiorhynchus parvicollis Gyllenhal, 1834affinis Hochhuth, 1847 (Otiorhynchus (Choilisanus)), Lectotype; stat. rev. now a valid speciescaroli Stierlin, 1893 (Otiorhynchus (Choilisanus)), Lectotypecaucasicus Stierlin, 1872 (Otiorhynchus (Choilisanus)), Lectotypeschoenherri Stierlin, 1877 (Otiorhynchus (Choilisanus)), Lectotype now a synonym of Otiorhynchus caucasicus Stierlin, 1872viridisetosus Stierlin, 1905 (Otiorhynchus (Choilisanus)), Lectotype; syn. n. of Otiorhynchus caucasicus Stierlin, 1872jaltensis Formanek, 1926 (Otiorhynchus (Egydelenus)), Lectotypebanaticus Stierlin, 1861 (Otiorhynchus (Elechranus)), Lectotypechalceus Stierlin, 1861 (Otiorhynchus (Elechranus)), Lectotyperoubali Penecke, 1931 (Otiorhynchus (Elechranus)), Lectotype; comb. n. hitherto Otiorhynchus (Cryphiphorus) roubalimus Stierlin, 1862 (Otiorhynchus (Ergiferanus)), Lectotype; comb. n. hitherto Otiorhynchus muschaudoiri Hochhuth, 1851 (Otiorhynchus (Lolatismus)), Lectotypedepressus Stierlin, 1875 (Otiorhynchus (Lolatismus)), Lectotype; comb. n. hitherto Otiorhynchus depressusbrevipennis Stierlin, 1892 (Otiorhynchus (Melasemnus)), Lectotypecrucirostris Hochhuth, 1851 (Otiorhynchus (Melasemnus)), Lectotype now a synonym of Otiorhynchus ovalipennis Boheman, 1843laconicus Kirsch, 1880 (Otiorhynchus (Meriplodus)), Lectotypeastutus (Faust, 1886) (Otiorhynchus (Mitomiris)), Lectotype described as Brachyrrhinus (Tournieria) astutuslaniger Faust, 1887 (Otiorhynchus (Mitomiris)), Lectotypepseudomias Hochhuth, 1847 (Otiorhynchus (Namertanus)), Lectotypeproximus Stierlin, 1861 (Otiorhynchus (Nihus)), Lectotypepunctirostris Stierlin, 1883 (Otiorhynchus (Nubidanus)), Lectotyperuminalis Faust, 1894 (Otiorhynchus (Nubidanus)), Lectotyperutilipes Hochhuth, 1851 (Otiorhynchus (Osmobodes)), Lectotype now a synonym of Otiorhynchus cribrosicollis Boheman, 1843tenuimanus Faust, 1890 (Otiorhynchus (Osmobodes)), Lectotypevernalis Faust, 1888 (Otiorhynchus (Osmobodes)), Lectotype; comb. n. hitherto Otiorhynchus vernalisdesbrochersi Stierlin, 1883 (Otiorhynchus (Otiomimus)), Lectotypeamabilis Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotype now a synonym of Otiorhynchus amplipennis Fairmaire, 1859auropupillatus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotypedelatus Faust, 1899 (Otiorhynchus (Otiorhynchus)), Lectotypelatissimus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotypescaberrimus Stierlin, 1861 (Otiorhynchus (Otiorhynchus)), Lectotypesteppensis Faust, 1888 (Otiorhynchus (Otiorhynchus)), Lectotype now a synonym of Otiorhynchus concinnus Gyllenhal, 1834auroguttatus Stierlin, 1879 (Otiorhynchus (Otismutilus)), Lectotype; stat. n.; comb. n. now a valid species; hitherto Otiorhynchus (Rusnepranus) auroguttatusnuncius Faust, 1890 (Otiorhynchus (Paracryphiphorus)), Lectotypecrinitarsis Stierlin, 1861 (Otiorhynchus (Petalorrhynchus)), Lectotype now a synonym of Otiorhynchus cupreosparsus (Fairmaire, 1859)patruelis Stierlin, 1861 (Otiorhynchus (Phalantorrhynchus)), Lectotypeplanidorsis Stierlin, 1886 (Otiorhynchus (Phalantorrhynchus)), Lectotype now a synonym of Otiorhynchus moestus Gyllenhal, 1834schneideri Stierlin, 1876 (Otiorhynchus (Pliadonus)), Lectotype; comb. n. hitherto Otiorhynchus schneiderisiewersi Faust, 1888 (Otiorhynchus (Pliadonus)), Lectotype, comb. n. hitrherto Otiorhynchus (Melasemnus) siewersialaianus Stierlin, 1886 (Otiorhynchus (Podonebistus)), Lectotype; comb. n. hitherto Otiorhynchus alaianusbleusei Faust, 1899 (Otiorhynchus (Podonebistus)), Lectotypecylindricus Stierlin, 1877 (Otiorhynchus (Podonebistus)), Lectotypenefandus Faust, 1888 (Otiorhynchus (Podonebistus)), Lectotypeprostratus Heyden, 1886 (Otiorhynchus (Podonebistus)), Lectotype; comb. n. hitherto Otiorhynchus prostratussubparallelus Stierlin, 1893 (Otiorhynchus (Podonebistus)), Lectotype; syn. n. of Otiorhynchus (Podonebistus) cylindricus Stierlin, 1877gelidus Gistel, 1857 (Otiorhynchus (Postaremus)), Neotype; syn. n. of Otiorhyrhynchus nodosus (O. F. Müller, 1754)popovi Faust, 1888 (Otiorhynchus (Prototis)), Lectotypecarbonarius Hochhuth, 1847 (Otiorhynchus (Provadilus)), Lectotypeargillosus Hochhuth, 1851 (Otiorhynchus (Pseudocryphiphorus)), Lectotypeirritabilis (Faust, 1886) (Otiorhynchus (Pseudocryphiphorus)), Lectotype described as Brachyrrhinus irritabiliszebei Stierlin, 1861 (Otiorhynchus (Pseudocryphiphorus)), Lectotypeauripes Stierlin, 1875 (Otiorhynchus (Rimenostolus)), Lectotype; comb. n. hitherto Otiorhynchus (Panorosemus) auripesarenosus Stierlin, 1861 (Otiorhynchus (Rusnepranus)), Lectotypeheerii Stierlin, 1858 (Otiorhynchus (Rusnepranus)), Lectotype; comb. n. hitherto Otiorhynchus (Otismotilus) heeriierroneus (Faust, 1886) (Otiorhynchus (Stupamacus)), Lectotype; stat. n. now a valid speciesinfensus Faust, 1888 (Otiorhynchus (Stupamacus)), Lectotype; comb. n. hitherto Otiorhynchus (Microphalantus) infensuspilosulus Penecke, 1928 (Otiorhynchus (Stupamacus)), Lectotype now a synonym of Otiorhynchus clavalis Apfelbeck, 1922cornicinus Stierlin, 1861 (Otiorhynchus (Tournieria)), Lectotypeemgei Stierlin, 1887 (Otiorhynchus (Tournieria)), Lectotypelubriculus Faust, 1890 (Otiorhynchus (Tournieria)), Lectotypekoenigi Faust, 1888 (Otiorhynchus (Udonedus)), Lectotypetruncatus Stierlin, 1861 (Otiorhynchus (Urorrhynchus)), Lectotypehystericus Faust, 1892 (Otiorhynchus (Zariedus)), Lectotypesedulus Faust, 1894 (Otiorhynchus (Zariedus)), Lectotype